4(2x-3)=-8x+4

Simple and best practice solution for 4(2x-3)=-8x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-3)=-8x+4 equation:



4(2x-3)=-8x+4
We move all terms to the left:
4(2x-3)-(-8x+4)=0
We multiply parentheses
8x-(-8x+4)-12=0
We get rid of parentheses
8x+8x-4-12=0
We add all the numbers together, and all the variables
16x-16=0
We move all terms containing x to the left, all other terms to the right
16x=16
x=16/16
x=1

See similar equations:

| -24=-4+5x | | (3/4)x+5-(1/2)x=3 | | (6x12-7)+2x12+(103+-1x12)=180 | | 5(2w+7)=75+5w | | 10x+35-9x=-28-6x | | 32/c=8 | | 15(2x+7)=5(3x+36) | | 2(4x+3)=9(x-1) | | 3(d+1)=15 | | 15x+23(x-5)=227 | | x2+18x+6=0 | | k-76/9=2 | | 82+x=3.7 | | 6(j+2)-1=83 | | -22=y-21 | | 7p+2p-6=12 | | 4(4+x)-20=8 | | 7(8-3x)=-112 | | 27x—8=-170 | | y+340=1.6 | | 96=4(s=11) | | -47=8-f | | y/4+2=-7 | | -8w-2w=-70 | | 3|4x+40|=36 | | 4m+33=8m+5 | | 8(d-91)+23=47 | | F(x)=x3-3x+8 | | 12=-6(7+u) | | 2.6x-6.7+8x=8.6x-15.3 | | -v1+1=-1+8v | | 5m-7m+5=4m-7 |

Equations solver categories